vault backup: 2025-02-16 19:02:21
This commit is contained in:
parent
763c9022ca
commit
c21c741225
27
.obsidian/plugins/obsidian-git/data.json
vendored
27
.obsidian/plugins/obsidian-git/data.json
vendored
@ -1,27 +0,0 @@
|
|||||||
{
|
|
||||||
"commitMessage": "vault backup: {{date}}",
|
|
||||||
"autoCommitMessage": "vault backup: {{date}}",
|
|
||||||
"commitDateFormat": "YYYY-MM-DD HH:mm:ss",
|
|
||||||
"autoSaveInterval": 5,
|
|
||||||
"autoPushInterval": 0,
|
|
||||||
"autoPullInterval": 5,
|
|
||||||
"autoPullOnBoot": true,
|
|
||||||
"disablePush": false,
|
|
||||||
"pullBeforePush": true,
|
|
||||||
"disablePopups": false,
|
|
||||||
"listChangedFilesInMessageBody": false,
|
|
||||||
"showStatusBar": true,
|
|
||||||
"updateSubmodules": false,
|
|
||||||
"syncMethod": "merge",
|
|
||||||
"customMessageOnAutoBackup": false,
|
|
||||||
"autoBackupAfterFileChange": false,
|
|
||||||
"treeStructure": false,
|
|
||||||
"refreshSourceControl": true,
|
|
||||||
"basePath": "",
|
|
||||||
"differentIntervalCommitAndPush": false,
|
|
||||||
"changedFilesInStatusBar": false,
|
|
||||||
"showedMobileNotice": true,
|
|
||||||
"refreshSourceControlTimer": 7000,
|
|
||||||
"showBranchStatusBar": true,
|
|
||||||
"setLastSaveToLastCommit": false
|
|
||||||
}
|
|
@ -15,6 +15,15 @@ If we have the coordinate pair $(a, f(a))$, and the value $h$ is the distance be
|
|||||||
$$\lim_{h \to 0}\dfrac{f(a + h) - f(a)}{h}$$
|
$$\lim_{h \to 0}\dfrac{f(a + h) - f(a)}{h}$$
|
||||||
The above formula can be used to find the *derivative*. This may also be referred to as the *instantaneous velocity*, or the *instantaneous rate of change*.
|
The above formula can be used to find the *derivative*. This may also be referred to as the *instantaneous velocity*, or the *instantaneous rate of change*.
|
||||||
|
|
||||||
|
## Examples
|
||||||
|
|
||||||
|
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||||
|
|
||||||
|
1. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||||
|
2. $= 4x^\frac{1}{3} - x^{-6}$
|
||||||
|
3. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||||
|
4. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||||
|
5. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
||||||
# Point Slope Formula (Review)
|
# Point Slope Formula (Review)
|
||||||
$$ y - y_1 = m(x-x_1) $$
|
$$ y - y_1 = m(x-x_1) $$
|
||||||
Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation:
|
Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation:
|
||||||
@ -114,9 +123,9 @@ $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
|||||||
> Given the function $(x^2+3)^4$, find the derivative.
|
> Given the function $(x^2+3)^4$, find the derivative.
|
||||||
|
|
||||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||||
1. First find the derivative of the outside function function ($f(x) = x^4$):
|
6. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
||||||
2. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
7. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||||
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
||||||
> Apply the chain rule to $x^4$
|
> Apply the chain rule to $x^4$
|
||||||
|
|
||||||
@ -152,18 +161,8 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|||||||
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
||||||
|
|
||||||
Given these facts:
|
Given these facts:
|
||||||
1. Let $y$ be some function of $x$
|
8. Let $y$ be some function of $x$
|
||||||
2. $\dfrac{d}{dx} x = 1$
|
9. $\dfrac{d}{dx} x = 1$
|
||||||
3. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
10. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||||
What's the derivative of $y^2$?
|
|
||||||
$\dfrac{d}{dx} y^2 = 2(y)^1 *\dfrac{dy}{dx}$
|
|
||||||
|
|
||||||
# Examples
|
## Examples
|
||||||
|
|
||||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
|
||||||
|
|
||||||
4. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
|
||||||
5. $= 4x^\frac{1}{3} - x^{-6}$
|
|
||||||
6. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
|
||||||
7. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
|
||||||
8. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
|
||||||
|
Loading…
x
Reference in New Issue
Block a user